Teacher training: the context of the COVID-19 pandemic and university teaching activities in Brazil - Pereira, Higinalice da Silva (2021)
The pandemic caused by the new coronavirus has affected society in several ways. With regard to teaching and the need to adapt to the recommendations of health organizations, institutions sought remote educational activities strategies, an alternative to keep their students in academic activities. The objective was an integrative review defining the challenges and possibilities found by educators in the teaching-learning process and didactics in the virtual space in this emergency change. The research was carried out in the Scielo, Capes Periodicals and Virtual Health Library (VHL) electronic databases, searching for publications in article format, covering the period from 2020 to 2021, considering the descriptors: “higher education” “COVID-19 ” “online teaching” ”teacher” and applying inclusion and exclusion criteria.56 articles (n=56) were found, which were reduced to (n=13) after analysis. The data report that the race to ensure the continuity of education and the lack of training and continuing education for the management of digital technologies resulted in the promotion of remote classes at various levels and despite efforts, emergency remote teaching brought negative implications in the process of teaching-learning. However, some works report that when you have knowledge about the tool, it is possible to increase student engagement in classes. We hope to contribute both to the critical reflection on the continuing education of higher education teachers and to foster discussions on the integration of TDIC into the curriculum on Higher Education.